A "Szeged Regionális Hulladékgazdálkodási Program" ISPA projekt megvalósult beruházásainak üzemeltetési tapasztalatai - Szabó, Ferenc; Keczer, Gabriella (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
In my paper I analyze the operational experiences of the „Szeged Regional Waste Management Program" ISPA project. On the basis of the case study we can conclude, that the outcomes of engineering, PR and procurement projects turn to be trouble-free, but facilities implemented in the frame of constructional projects suffer several difficulties when operated. Thus, the operational problems are not necessary, but are the consequences of the tender procedures. The main reasons are the lack of professionalism, the consciously underestimated implementation costs on the side of the contractor, and the lack of cooperation between the main actors of the project.